Comparisons of pregnancy outcomes between twin pregnancies with and without second‐trimester amniocentesis. (4th August 2020) - Dechnunthapiphat, Rangsan; Sekararithi, Ratanaporn; Tongsong, Theera; Wanapirak, Chanane; Piyamongkol, Wirawit; Sirichotiyakul, Supatra; Tongprasert, Fuanglada; Srisupundit, Kasemsri; Luewan, Suchaya; Jatavan, Phudit; Traisrisilp, Kuntharee
Abstract: Objective: To assess the amniocentesis‐related pregnancy loss rate and preterm birth rate among twin pregnancies undergoing amniocentesis. Methods: A retrospective cohort study was conducted at a tertiary center. The study group included twin pregnancies undergoing amniocentesis during 16 to 22 weeks of gestation. The control group was those not undergoing amniocentesis. All amniocenteses were performed by the MFM specialists. The main outcomes were the rate of pregnancy loss (before 24 weeks) and preterm birth. Results: A total of 332 cases in the study group and 1188 controls were analyzed. The percentages of maternal age ≥35 years, high parity, and cases complicated with medical diseases were significantly higher in the study group. The pregnancy loss rate after the procedure tended to be higher, but not significant, in the study group (3.0% vs 2.2% P = .383). Likewise, the rate of preterm birth in the study group was higher, but not significant (70.5% vs 66.0% P = .130). Logistic regression analysis to adjust confounding factors showed no significance of amniocentesis on pregnancy loss and preterm birth. Conclusion: Though amniocentesis in twin pregnancies has theoretical risk of pregnancy loss, it is relatively safe when performed by maternal–fetal medicine specialists. This information is useful for counseling, especially when performed by experienced hands.